Management of adhesive capsulitis of shoulder joint by single platelet rich plasma injection - Alok Chandra Agrawal; Buddhadeb Nayak; Harshal Sakale (Journal of Orthopedics, Traumatology and Rehabilitation, 2019)
Introduction: Adhesive capsulitis of shoulder is a condition characterized by painful and global restriction of active and passive glenohumeral range of motion in at least two directions, most notably shoulder abduction and external rotation. Platelet-rich plasma (PRP) is an emerging treatment option and its efficacy needs to be examined. Aim: The aim of the study is to assess the efficacy of PRP injection in the treatment of adhesive capsulitis of the shoulder joint. Materials and Methods: Patients with adhesive capsulitis received a single injection of PRP (4 ml) (n = 20). All participants were also advised to perform a home-based 10 min exercise therapy after injection. The outcome was measured using Constant and Murley shoulder score. Participants were evaluated at 0, 3rd day, and 1 month. Unpaired t-test tests were used to determine significant differences. Results: PRP treatment showed increase in pain for few participants at the 3rd day, causing decreased active range of motion. However, at 1 month, PRP treatment resulted in statistically significant improvements in constant score. No major adverse effect was seen in PRP injection. Conclusion: This study demonstrates that single injection of PRP improves both in pain and all range of motion of shoulder joint.